KEPENTINGAN ASEAN DALAM PEMBENTUKAN ASEAN+3 MACROECONOMIC RESEARCH OFFICE (AMRO) TAHUN 2011 - Mardiana, Dian; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This thesis is based on the author’s interest in the establishment of the ASEANinterests AMRO as a form that can synergize economical interconnectivity betweencountries in the ASEAN +3 region and is expected to be a recognized as a form ofsurveillance institute in Southeast Asia and three countries involved in the East Asiancooperation namely ASEAN +3, which were: Japan, China and South Korea.Keyword: AMRO, ASEAN+3, economical sinergize